2009 Sixth International Conference on Information Technology: New Generations 2009
DOI: 10.1109/itng.2009.317
|View full text |Cite
|
Sign up to set email alerts
|

Google Scholar's Ranking Algorithm: The Impact of Articles' Age (An Empirical Study)

Abstract: Google Scholar is one of the major academic search engines but its ranking algorithm for academic articles is unknown. In recent studies we partly reverse-engineered the algorithm. This paper presents the results of our third study. While the first study provided a broad overview and the second study focused on researching the impact of citation counts, the current study focused on analyzing the correlation of an article's age and its ranking in Google Scholar. In other words, it was analyzed if older/recent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
0
26
1
1
Order By: Relevance
“…PubMed uses algorithms based on MeSH terms and reports the most recent articles at the top of the list (which likely have not had adequate time to be appropriately cited). In contrast, research studies on Google Scholar's proprietary algorithms have demonstrated that the number of citations is an important criterion in the initial list of articles and that the date of publication is not an important criterion . In our study, the median publication dates for articles retrieved by Google Scholar searches were earlier than those retrieved from the PubMed database.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…PubMed uses algorithms based on MeSH terms and reports the most recent articles at the top of the list (which likely have not had adequate time to be appropriately cited). In contrast, research studies on Google Scholar's proprietary algorithms have demonstrated that the number of citations is an important criterion in the initial list of articles and that the date of publication is not an important criterion . In our study, the median publication dates for articles retrieved by Google Scholar searches were earlier than those retrieved from the PubMed database.…”
Section: Discussioncontrasting
confidence: 82%
“…In our study, Google Scholar searches retrieved category 1, 2 articles with a higher median number of citations. As discussed above, this result is explained at least partially by Google Scholar's ranking strategies to identify articles with higher number of citations . Kalkarni et al .…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, SEO has also been applied to academic search engines, such as Google Scholar and Microsoft Academic. This new application has received the name of "academic SEO" (or ASEO) [22][23][24][25][26]. ASEO helps authors and publishers to improve the visibility of their publications, thus increasing the chances that their work will be read and cited.…”
Section: Introductionmentioning
confidence: 99%
“…Do citations received have a similarly strong influence on all these systems? A similar approach to the one adopted here has been taken in previous studies of the factors involved in the ranking of scholarly literature [22,23,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies we researched the ranking algorithm of Google Scholar [1][2][3] and gave advice to researchers on how to optimize their scholarly literature for Google Scholar [4]. However, there are provisos in the academic community against what we called "Academic Search Engine Optimization" [4].…”
Section: Introductionmentioning
confidence: 99%